Equity valuation of Yandex - Faleev, Pavel (2018)
The purpose of this thesis is evaluating of Russian internet company and obtaining the Yandex Equity Fair Value. In order to achieve the most accurate results the analysis of literature was provided, and two appropriate valuation methods were chosen: Discounted Cash Flow Model and Relative Valuation Method. By applying DCF method, the target price achieved was $31.75 based on the assumptions about future company revenue growth and about a number of other variables. Relative Valuation based on the Market Multiples gave a $30.23 per share. As a result, the average target price was $31 per Yandex share. In order to predict the outcome of share price given a range of assumed variables, the sensitivity analysis was run. As a result of Yandex Equity Valuation a HOLD recommendation for investors was given. Finally, the comparison of results with Sberbank CIB Investment Research of Yandex was provided.